(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2025)
Sustainable Development Goals is an off-shoot of Millennium Development Goals after the life span of the latter terminated in 2015. This paper argue that administrators at the local level are instrumental to the successful implementation of the agenda. There exists substantial evidences that suggests that, in spite of the claims by state officials to the contrary, the pace of achievement of SDG goals, after almost a decade of its launch remains abysmally low. This study, therefore, assessed the involvement of local administrators in the SDG implementation framework. The study adopts a explanatory design and qualitative method of data collection and analysis were adopted. The paper found, against speculations, that the local administrators had in-depth knowledge about SDGs agenda and they were instrumental to its implementation. The paper recommends a bottom up strategy that will start with localising SDG from the third tier level of governance and implementing same therefrom using trained administrators as key role players.